2012
DOI: 10.4028/www.scientific.net/amm.253-255.385
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Impact of Admixture for Concrete Heat of Hydration and Early-Age Contractile Properties

Abstract: During the technology development of modem concrete, concrete structure crack (especially early-age crack) becomes more and more serious and has been one of main research directions of civil engineering. This paper aims at the seriousness of concrete structure crack and presents one of main cause is that concrete early-age (especially autogenous shrinkage) become large through the experimental study. autogenous shrinkage are mainly belongs to temperature cracks and desiccation cracks. Analyses the affection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Some concrete products are typically made with a specific class of cement. For instance, concrete in very large foundations will use ggbfs to reduce the heat of hydration and prevent cracking (Sun et al, 2013;Tang et al, 2015). This kind of information is not available for most applications.…”
Section: Mapping Materials Flowmentioning
confidence: 99%
“…Some concrete products are typically made with a specific class of cement. For instance, concrete in very large foundations will use ggbfs to reduce the heat of hydration and prevent cracking (Sun et al, 2013;Tang et al, 2015). This kind of information is not available for most applications.…”
Section: Mapping Materials Flowmentioning
confidence: 99%
“…is is well explained by equation (16). In the stage of increasing concrete temperature, when the concrete structure is thinner, (Q rise /Q total ) is smaller and (Q lost /Q total ) is larger, so the T max decreases more; at the same time, boundary conditions affect the value of (Q lost /Q total ), so different boundary conditions have different effects.…”
Section: Discussionmentioning
confidence: 97%
“…As an effective means to improve the thermal and mechanical properties of concrete, concrete admixtures have been widely used in engineering [13][14][15]. Commonly used concrete admixtures include water-reducing agents, retarders, air-entraining agents, etc., among which water-reducing agents can reduce the use of water and reduce the heat released by the hydration reaction [16].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that fly ash and granulated blast furnace slag significantly increased the workability and compression strength of self-compacting concrete mixtures, and the best resistance to sodium and magnesium sulphate attacks was obtained from a combination of 40% granulated blast furnace slag with 60% cement. In addition, the use of mineral admixtures to replace cement in concrete can effectively save engineering costs, reduce the early hydration heat of concrete, and the thermal expansion coefficient of cement slurry, resulting in the reduction of concrete shrinkage and crack formation [ 16 ]. Zhang et al [ 17 ] evaluated the effect of mineral admixtures on the hydration heat of the binder paste in high-performance concrete and found that mineral admixtures greatly reduced the hydration heat and the exothermic rate and prolonged the arrival time of the highest temperature, particularly when two or three types of mineral admixtures were added at the same time.…”
Section: Introductionmentioning
confidence: 99%